2006
DOI: 10.1021/jf0609734
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection and Identification of Pseudomonas aeruginosa and Escherichia coli as Pure and Mixed Cultures in Bottled Drinking Water Using Fourier Transform Infrared Spectroscopy and Multivariate Analysis

Abstract: Fourier transform infrared (FT-IR) spectroscopy and multivariate analysis were used to identify Pseudomonas aeruginosa and Escherichia coli ATCC 25922 inoculated into bottled drinking water. Three inoculation treatments were examined: (i) E. coli ATCC 25922 (N = 3), (ii) P. aeruginosa (N = 3), and (iii) a 1:1 (v:v) mixed culture of both P. aeruginosa and E. coli ATCC 25922 (N = 3). The control treatment was noninoculated drinking water (N = 3). Second derivative transformation and loadings plots over the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 26 publications
1
59
0
2
Order By: Relevance
“…The second loading of the treated and control groups indicated that the obvious regions at 3000-2800 cm -1 (~2963, ~2921, ~2875, ~2852 cm -1 ) could be attributed to the stretching modes of CH 2 and CH 3 in the fatty acids located on the various membrane amphiphiles and ester bands, respectively (Figure 4d) [25,26]. The treated cells exhibited a peak area and intensity at ~2921 and ~2852 cm -1 , respectively, of ceftazidime > control > ceftazidime plus baicalein (Figure 4d) [23,27].…”
Section: Ft-ir Spectramentioning
confidence: 96%
See 1 more Smart Citation
“…The second loading of the treated and control groups indicated that the obvious regions at 3000-2800 cm -1 (~2963, ~2921, ~2875, ~2852 cm -1 ) could be attributed to the stretching modes of CH 2 and CH 3 in the fatty acids located on the various membrane amphiphiles and ester bands, respectively (Figure 4d) [25,26]. The treated cells exhibited a peak area and intensity at ~2921 and ~2852 cm -1 , respectively, of ceftazidime > control > ceftazidime plus baicalein (Figure 4d) [23,27].…”
Section: Ft-ir Spectramentioning
confidence: 96%
“…The biomolecule fingerprint clusters for the control and the ceftazidime alone or in combination with baicalein groups were clearly differentiated [23,27].…”
Section: Ft-ir Spectramentioning
confidence: 99%
“…FTIR methods combined with various chemometric analyses procedures [28][29][30] can be applied to the ield of medical applications, pharmaceutical industry, and food microbiology, comprising the detection of bacteria from culture and food, discrimination between various microbial species and strains, classiication of a diversity of microorganisms at genus, species, and subspecies levels, bacteria viability analysis, characterization growth-dependent phenomena and cell-drug interactions, investigation in situ intracellular components or structures such as inclusion bodies (IBs), storage materials, or endospores [31]. Because in biological and in medical ield, protein aggregation represents an important issue encountered in the expression of recombinant proteins in bacterial cells in the form of IBs and in some diseases, the monitoring in vivo of the kinetics of protein aggregation in Escherichia coli within intact cells using the FTIR spectroscopy methods constitutes a fast and a facile technique used to acquire structural information on proteins within IBs [32].…”
Section: Recent Applications Of Fourier Transform Infrared Spectroscomentioning
confidence: 99%
“…4) [29,30]. The spectral analysis of vibration modes in this range included m s CH 2 (2863-2843 cm À1 ), m s CH 3 (2882-2862 cm À1 ), m as CH 2 (2936-2916 cm À1 ), and m as CH 3 (2972-2952 cm À1 ) [10,23,24,29].…”
Section: Identification By Spectral Band Of Cell Wall Constituent LImentioning
confidence: 99%